2019
DOI: 10.1016/j.cell.2019.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Dependent and -Independent Roles of E3 Ligase RIPLET in Innate Immunity

Abstract: Highlights d RIPLET, not TRIM25, is the obligatory ubiquitin E3 ligase for RIG-I d RIPLET recognizes pre-assembled RIG-I oligomers on dsRNA and ubiquitinates RIG-I d RIPLET can cross-bridge RIG-I filaments formed on longer dsRNA d The two binding modes synergize for length dependent dsRNA discrimination by RIG-I

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
174
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(189 citation statements)
references
References 61 publications
8
174
0
Order By: Relevance
“…In particular, recent work by Cadena et al showed that deletion of TRIM25 from HEK293T and MEF cells results in an increase, not a reduction in RIG‐I activation in response to 5′ppp‐RNA. In contrast, deletion of Riplet from the same cell line results in complete abolition of RIG‐I signaling, to the same level as deletion of RIG‐I itself (Cadena et al, ). The same was found to be true for expression of IFNβ mRNA in response to infection with Sendai virus, with deletion of TRIM25 in this case resulting in a significant increase in IFNβ expression (Cadena et al, ).…”
Section: Trim25's Role In Innate Immunitymentioning
confidence: 98%
See 2 more Smart Citations
“…In particular, recent work by Cadena et al showed that deletion of TRIM25 from HEK293T and MEF cells results in an increase, not a reduction in RIG‐I activation in response to 5′ppp‐RNA. In contrast, deletion of Riplet from the same cell line results in complete abolition of RIG‐I signaling, to the same level as deletion of RIG‐I itself (Cadena et al, ). The same was found to be true for expression of IFNβ mRNA in response to infection with Sendai virus, with deletion of TRIM25 in this case resulting in a significant increase in IFNβ expression (Cadena et al, ).…”
Section: Trim25's Role In Innate Immunitymentioning
confidence: 98%
“…This is followed by ubiquitination at various sites on the 2CARD by Riplet, TRIM25, TRIM4 and MEX3C. This would fit with several recent observations (Cadena et al, ; Hayman et al, ; Shi et al, ) that Riplet is absolutely required for efficient RIG‐I signaling activation, while TRIM25 is not, as well as explaining why there is seemingly redundancy between the other E3 ligases. In particular, recent work by Cadena et al showed that deletion of TRIM25 from HEK293T and MEF cells results in an increase, not a reduction in RIG‐I activation in response to 5′ppp‐RNA.…”
Section: Trim25's Role In Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Much of viral sensing and immune response mechanisms derive from functional and structural studies of RIG-I (Yoneyama and Fujita, 2008). Upon binding to dsRNA, RIG-I transforms from an auto-repressed to an open conformation (Kowalinski et al, 2011); this facilitates its tetramerisation and K63-linked ubiquitylation by either TRIM25 or RIPLET (Cadena et al, 2019;Gack et al, 2007). RIG-I tetramers translocate to mitochondrial membranes (Liu et al, 2012) where they interact with mitochondrial antiviral signaling (MAVS) protein via their respective CARD domains.…”
mentioning
confidence: 99%
“…Until recently K63 ubiquitylation was thought to be catalysed interchangeably by TRIM25 and RIPLET; however, recent studies have indicated that RIG-I activation is fundamentally dependent on RIPLET (Cadena et al, 2019).…”
mentioning
confidence: 99%